X-ray absorption and magnetic circular dichroism characterizations of Mn doped ZnO - Thakur, P.; Chae, K. H.; Kim, J.-Y.; Subramanian, M.; Jayavel, R.; Asokan, K. (AMER INST PHYSICS, 2007)
We report the near-edge x-ray absorption fine structure (NEXAFS) and x-ray magnetic circular dichroism (XMCD) experiments on well characterized Mn doped ZnO thin films that show ferromagnetism at room temperature. The NEXAFS measurements at O K edge clearly exhibit a preedge spectral feature which evolves with Mn doping, similar to one observed in hole-doped cuprates and manganites. The Mn L-3,L-2 edge NEXAFS spectra exhibit divalent Mn apart from mixed valent Mn3+/Mn4+ states. The spectral features of XMCD at Mn L-3,L-2 edge demonstrate that ferromagnetism comes from Mn2+ ions and its dichroism shape is independent of Mn concentration. (C) 2007 American Institute of Physics.
Keywords: FERROMAGNETISM; SEMICONDUCTORS; SPECTROSCOPY; TEMPERATURE